IDENTIFIKASI KANDUNGAN ZAT BESI DAN VITAMIN C PADA DAUN KELOR (MORINGA OLEIFERA) SEBAGAI PENANGANAN ANEMIA PADA IBU HAMIL - Dian Soekmawaty Riezqy Arienda; Irni Setyawati; Kusniyati Utami; Hardaniyati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
hemoglobin levels. Anemia in pregnancy is a condition where hemoglobin is below normal, which is below 11 g/dl. The most common cause of anemia in pregnancy is iron deficiency. Moringa leaves are one type of food that is rich in iron which can overcome anemia. Methods Methods The method in this study was to conduct laboratory tests on 100 grams of fresh Moringa leaves colored from light green to slightly dark green. Screening for Fe used Potassium tocyanide/Ammonium thiocyanate 2 NDragendorff reagent, while vitamin C with 10% povidone iodine reagent was equivalent to 1% iodine. Results The results showed that Moringa leaves (Moringa oleifera) contained Fe and Vitamin C compounds. Discussion/Suggestion The use of Moringa leaves is an alternative that can be used to prevent anemia, besides being cheap and easy to obtain. It is expected that pregnant women besides taking Fe tablets are also advised to consume foods high in iron such as Moringa leaves to increase hemoglobin in pregnant women. Further researchers are advised to conduct research related to development innovation